Firm's productivity, investment and training: What happened during the recession and how was it affected by the national minimum wage? A report to the low pay commission - Claire Crawford; Wenchao Jin; Helen Simpson (Institute for Fiscal Studies (IFS), 2013)
In 2008-09, the UK experienced its deepest recession since the Second World War. One notable feature of this recession was, however, the resilience of employment, which fell by just 2.1% at a time when GDP fell by 6.3%. This suggests that firms may have been trying to weather the recession by holding on to their workers and reducing their hours, rather than making them redundant. Such behaviour is sometimes thought to indicate 'labour hoarding'.This report uses business data to document what happened to a variety of indicators of labour hoarding, as well as investment and training, over the course of the 2008-09 recession. In particular, it shows how these patterns vary amongst different types of firms, including by size and coverage of the National Minimum Wage (NMW) (i.e. the proportion of workers who are paid at or below this level). The report is associated with the Low Pay Commission Report 2013 and is funded by the Low Pay Commission.
Keywords: 330